Relationship of Working Period in Tobacco Industry with Cervical Precancerous - Nur Venny Ratnasari; Afnani Toyibah (Universitas Airlangga, 2018)
Background: Cervical cancer prevalence ranks 7th globally and number 8th as the cause of death. Cervical cancer is ranked 2nd out of the 10 most cancers in Indonesia with an prevalence of 12,70%. Purpose: The aim of this research was to identify the relationship between females working period and the cervical precancerous lesions on female workers in “J” tobacco industry. Methods: This research was an analytical study using cross sectional design. The population of this research was female workers of